2005
DOI: 10.1590/s0034-71672005000300014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da realização e do registro da Sistematização da Assistência de enfermagem (SAE) em um hospital universitário

Abstract: This descriptive study was carried out in a teaching hospital at São Paulo city and had as objective to identify the phases performance and registration of nursing care systematization and the most frequent nursing diagnoses. Data were collected retrospectively from 135 patients records of three units: Cardiology, Adult Infectious Diseases and Neurosurgery, from January to July, 2002. The phases: history, nursing diagnoses, prescription, evolution and assessment were performed and registered in the three units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
36

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 2 publications
3
16
0
36
Order By: Relevance
“…In this sense, the outcomes of this study support data in the literature in promoting the awareness of nurses to ensure continuous and complete records (8,(9)(10)16) . Regarding the presence of nursing care records (Table 1) findings highlighted the nursing history and physical examination with 99.6% and 94.6%, respectively, as the records fully completed.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this sense, the outcomes of this study support data in the literature in promoting the awareness of nurses to ensure continuous and complete records (8,(9)(10)16) . Regarding the presence of nursing care records (Table 1) findings highlighted the nursing history and physical examination with 99.6% and 94.6%, respectively, as the records fully completed.…”
Section: Discussionsupporting
confidence: 74%
“…The nurse, according to researchers, should not be restrained with respect to his creativity and the pursuit of clinical reasoning, but results of recent studies have shown that professionals are increasingly restricted to the implementation of nursing diagnoses and prescriptions that do not correspond to these, that is, they make diagnoses, but do not prescribe a related action; the opposite is also true (14,15) . Studies have shown that intelligently designed, nonstandardized forms, that offered space for the nurse to create, and which are directed toward the implementation of activities essential to care, have been facilitating the employment of clinical reasoning on the part of the professional, in order to optimize the relationship between prescription and diagnosis (6,10,14,16) . The literature demonstrates that the creation of intelligent forms is not sufficient for solving the difficulties encountered in relation to achieving the NRs (16,17) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Através de uma intervenção, proporciona os resultados que se esperam dela, pois, como intervenção terapêutica, o cuidado é centralizado nas necessidades do paciente que devem ser atendidas. A ação será de cuidado, se a enfermeira identifica uma necessidade e sabe o que fazer para atendê-la (13) .…”
Section: Discussionunclassified
“…A educação não é apenas um processo institucional e instrucional, mas também um instrumento formativo do humano, seja na particularidade da relação pedagógica pessoal, seja no âmbito da relação social coletiva sem perder as referências éticas e políticas, tendo como premissa que o processo de formação de um sujeito ético, ou de um cidadão, vai depender da própria construção do sujeito humano (2).…”
Section: Introductionunclassified